Frontispiece: Direct Measurement of the Isomerization Barrier of the Isolated Retinal Chromophore. Issue 16 (13th April 2015) - Dilger, Jonathan; Musbat, Lihi; Sheves, Mordechai; Bochenkova, Anastasia V.; Clemmer, David E.; Toker, Yoni
<x xml:space="preserve">Abstract</x> Isomerization In their Communication on page 4748 ff., Y. Toker and co‐workers report the energy barrier for the isomerization of the retinal protonated Schiff base chromophore and show that it is significantly lower than that within opsin proteins.